La Costituzione e il ruolo dell’Islam in Libia dall’indipendenza alla caduta di Moammar Gheddafi: origini e prospettive (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Introduzione - 2. La monarchia di Idris Al Senussi e la Costituzione del 1951 - 3. L’Islam nella Libia di Re Idris - 4. Moammar Gheddafi e la Terza Teoria Universale: l’Islam all’interno del “Nuovo” sistema libico - 5. Gheddafi e il movimento islamista - 6. La caduta di Gheddafi, la Dichiarazione Costituzionale del 2011 e l’Islam - 7. L’ultima bozza del 2017 e i contrasti infiniti - 8. Brevi riflessioni.The Constitution and the role of Islam in Libya from independence to the fall of Moammar Gaddafi: origins and perspectivesABSTRACT: This study aims to retrace Libya's constitutional path from Independence, obtained in December 1951, up to the "post-Gaddafi" era, which began with his fall in October 2011 and where the agreement on a new Constitution is still today - after more than ten years - one of the thorniest issues in the construction of a real Libyan State. Particular emphasis will be given to the religious aspect that has characterized the Constitutional Charter of Libya in its short national history and to the religious challenges faced in the different historical phases. The study will be divided into three parts. The first one will try to frame the constitutional discourse in the new independent Libya under the monarchy of King Idris al-Senussi. In the second part, will be addressed to the drastic changes that occurred with Moammar Gaddafi's rise to power. Finally, in the last part will try to draw a picture of what the situation is today and to understand what are actually the obstacles that are holding back an agreement between the rival factions (East and West) on a shared Constitution.